Thoracic nerve cord - ganglia recognition in intraspecific and interspecific transplants in the white shrimp, Penaeus (Litopenaeus) vannamei - Alfaro-Montoya, Jorge (2009)
The recognition response of Penaeus (Litopenaeus) vannamei against thoracic nerve cord–ganglia transplants from three species of Penaeidae: P. vannamei, P. (Litopenaeus) stylirostris, and Trachypenaeus byrdi, and one species of Palaemonidae: Macrobrachium tenellum, was evaluated. Implanted tissues were removed from recipients at the end of different incubation periods, catalogued based on three gross categories (missing, unmelanized, and melanized), and analyzed by histology. Some intraspecific implants of thoracic ganglia from P. vannamei were missing after a few weeks, without activating a haemocytic response leading to encapsulation. The same condition was observed for thoracic ganglia from P. stylirostris and T. byrdi. Unmelanized tissue sections from P. vannamei, P. stylirostris, and T. byrdi, were commonly recovered; however, most implants had a smaller size than their original length (5–6 mm). Intraspecific transplantation in P. stylirostris also generated a time-related reduction in graft size. Based on our observations, missing implants, small grafts and compacted structure of tissues indicate an absorption mechanism from the host without encapsulation. Histological analysis of unmelanized tissues from Penaeidae reveals that the structure of nerve cords is similar to controls, showing living nerve cord cells surrounded by the neurilemma, and no haemocytic encapsulation at the periphery. Neurosecretory cells were also observed alive, but the structure of ganglia was different from control ganglia. On the other hand, tissues from M. tenellum were all encapsulated, showing distinctive black depositions and the distinctive layers of haemocytes. These findings suggest that neither interspecific nor intraspecific thoracic ganglia transplants within Penaeidae keep their tissue integrity inside P. vannamei. The endocrine implications for inducing ovarian maturation have to be investigated